The potential use of YouTube in teaching and learning Oral Biology and Pathology among BDS students of BPKIHS, Nepal - Jain, Neetu; Keshwar, Shashi; Raut, Toniya; Agrawal, Navin; Singh, Vimmi (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Today, many students from various backgrounds turn to YouTube and other online learning platforms for supplementary information. In this research, we assessed the student’s opinions on the efficacy of YouTube for providing a high-quality education in the field of oral biology and oral pathology. Methods: In this study, the principal investigator conducted a classroom lecture on two selected topics for students from BDS 2nd and 3rd year and provided a YouTube video link of the same topic to the participants. The YouTube video on the topic was selected by the experts on the subject. Following this, the principal investigator collected the data from the students using a validated semistructured questionnaire. Results: Total 49(59%) participants strongly agreed that YouTube can be used effectively for understanding various oral biology and oral pathology topics, and 52(62.7%) of participants strongly agreed that YouTube is beneficial in teaching and learning various oral biology and oral pathology topics. However, 34(41%) of participants strongly agreed that YouTube is not the main learning tool but a support tool for providing information on various oral biology and oral pathology topics. Conclusions: It can be concluded from the results that teaching and learning oral biology and oral pathology is more efficient if coupled with YouTube applications.